Prevalence of anaemia among adolescent girls in a rural area of Central Kerala, South India - N., Divyamol; V., Sajna M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescence lays the foundation for future health. Anaemia among adolescent girls has become a significant public health issue. The state of Kerala has few reported studies in this regard. The current study was conducted to determine the prevalence of anaemia in adolescent girls in a rural area of central Kerala and to find out the factors associated with anaemia among them. Methods: A cross sectional study was conducted among 194 adolescent girls of Tholur panchayath in Thrissur district, Kerala. The study participants were randomly selected from the adolescent registers maintained in anganwadies. A semi-structured questionnaire was administered after getting informed assent and consent from the participants and their guardians respectively. All the participants were clinically examined, anthropometric measurements were taken and 2 CC of EDTA anti-coagulated blood samples were collected to test haemoglobin. Results: The prevalence of anaemia among the participants is found to be 26.3% (95% CI: 17.4-37.34). Out of the total anaemic girls, 94% were mildly anaemic (Hb between 10-11.9 g/dl) and the remaining were moderately anaemic (Hb between 7-9.9 g/dl). Anaemia was significantly higher in the age group between 10-14 years (39.5%), compared to 15-19 years (15.6%). Lower frequency of intake of green leafy vegetable and wholegrain cereals were found to have significant association with anaemia. Conclusions: Anaemia remains a moderate public health hazard among the adolescent girls, with roughly every fourth girl becoming anaemic. Nutritional inadequacies were shown to be the most common cause of anaemia, which was found to be greater in the early teenage period.